Achieving high porosity and large recovery strain in Ni-free high Zr-containing Ti-Zr-based shape memory alloy scaffolds by fiber metallurgy. (January 2021) - Li, Shuanglei; Kim, Yeon-wook; Choi, Mi-seon; Nam, Tae-hyun
Abstract: Highly porous Ti-40Zr-8Nb-2Sn (at.%) shape memory alloy scaffolds were prepared by fiber metallurgy using rapidly solidified alloy fibers for the application of cancellous bone replacement. The phase constituents of alloy fibers and scaffolds were investigated by means of X-ray diffraction (XRD), superelastic behavior of alloy fibers was investigated by means of the dynamic mechanical analyzer (DMA), microstructures and mechanical properties of scaffolds were investigated by means of scanning electron microscopy (SEM) and compressive test, respectively. As-spun alloy fibers consisted of only β phase at room temperature. Clear superelastic behavior was observed in the as-spun alloy fibers at temperatures between 153 K and 298 K. The scaffolds showed three-dimensional networks with fiber-fiber bonds, whose porosity and pore size was about 80% and larger than 100 μm, respectively. The compressive yield stress and elastic modulus of the scaffold annealed at 973 K for 1.8 ks were about 4.0 MPa and 0.3 GPa, respectively, similar to those of cancellous bone. Recoverable strain in the scaffold was improved from 2.8% to 4.0% after annealed at 973 K due to the absence of α phase formed in the as-sintered scaffold. Stable cyclic superelastic behavior was observed in the annealed scaffolds at room temperature. Highlights: Novel Ni-free high Zr-containing Ti-Zr-Nb-Sn alloy scaffolds with high porosity of 80% were prepared by fiber metallurgy. A large recoverable strain of 4.0% was obtained in the Ti-Zr-Nb-Sn scaffold at room temperature. The scaffolds showed an elastic modulus of 0.3 GPa, similar to that of cancellous bone. As-spun alloy fibers showed clear superelasticity at a temperature range of 153–298 K.